THE APPLICATION OF GARCH (1.1) MODEL FOR MESEARING SHOCKS TRANSMISSION IN BOND MARKET - Karkowska, Renata (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The object of the study is identification of the bond yields volatility in selected European countries, during the crisis of Greece’s public finances from 2010 to 2013. For this purpose used GARCH (1.1) model. The specific aim of the study is to determine: do we have to deal with so-called contagion effect in Treasury bonds market? The analysis was conducted in two trials : 1/ for the countries of Central and Eastern Europe, represented by Czech Republic and Poland, 2/ for developed countries – Austria and France.